Local Sources of Income, Capital Expenditures and Human Development Index: Evidence from Central Java, Indonesia - Ardiansyah Ardiansyah (The Indonesian Journal of Accounting Research, 2015)
The implementation of regional autonomy is to give authority to local governments in managing of local potentials to allocate revenues in fulfilling the public interest and enhance public welfare. The public welfare can be seen from the increasing of Human Development Index of the region through the allocation of capital expenditures. The objective of the research is to recognize the effects of the Local Own-source Revenue (PAD), the General Allocation Fund (DAU) and the Special Allocation Fund (DAK) towards the Capital Expenditures and the Quality of Human Development (which is measured by Human Development Index HDI). The sampling method used in this research is purposive sampling method, with total sample of 24 regencies/municipalities in Central Java. The research data used is the secondary data of the Regional Revenues and Expenditures Budget of regional government of regencies/municipalities in Central Java, which includes Local Own-source Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Regional Expenditures Actual Report and Human Development Index (HDI) in the fiscal years of 2010-2012. The results of this research show that the Local Own-source Revenue (PAD), the General Allocation Fund (DAU) and Special Allocation Fund (DAK) have simultaneously influence on the Human Development Index. Partially, only the Local Own-source Revenue (PAD) has positively influences to Human Development Index.